The Value of Different Radiological Modalities in Assessment of Spontaneous Pneumomediastinum: Case Review and Diagnostic Perspective - Poonam Singh Jariwala; Kaarthigeyan Kalaniti; Neil Wonko; Sibasis Daspal; Veronica Mugarab Samedi (Thieme Medical Publishers, Inc., 2019)
Abstract Pneumomediastinum (PM), or a mediastinal air leak, is a known morbidity in neonates. Among predisposing factors, the most significant are mixed lung diseases, such as pneumonia or meconium aspiration syndrome, with coexisting atelectasis and airway obstruction. We report an unusual presentation of significant spontaneous pneumomediastinum in a term newborn delivered by elective cesarean section with no history of active resuscitation at birth. Timely diagnosis of SPM is important for both management and prognosis. We believe that lung ultrasound (LUS) is a promising screening tool for early detection of PM in neonates, and could help avoid unnecessary exposure to radiation in delicate neonates. More simultaneous studies comparing chest X-ray (CXR), LUS, and computed tomography (CT) scans may help to prove the utility value of point-of-care ultrasounds as a primary diagnostic tool in identifying this morbidity.